2019
DOI: 10.3389/fonc.2019.00439
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of the Neo-Immunoscore in Renal Cell Carcinoma

Abstract: Objective: This study evaluated the prognostic value of the newly-built Immunoscore (neo-Immunoscore) in patients with renal cell carcinoma (RCC). Methods: Eighty-two patients with RCC were enrolled in this study. Their 3- and 5-year survival rates and overall survival (OS) were evaluated. The clinicopathologic data of the 82 patients were collected and analyzed. CD3, CD4, CD8, CD45RO, Foxp3, tumor necrosis factor receptor type II (TNFR2), programmed death ligand-1 (PD-L1), C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In one study in RCC, CD8+ T cell quantification on anti-PD-1 treated RCC samples found a majority of samples (73%) were infiltrated; however, infiltration did not correlate with PFS [69]. In another study, an 11-marker multiplex IF panel-based prognostic score associated with survival of RCC patients, particularly the density of T cell marker CD3-positive cell populations [159]. Interestingly, spatial immune profiling of nephrectomy samples revealed patients with excluded TME had reduced burden of metastatic disease and improved overall survival versus T cell-inflamed TME [160].…”
Section: Immunofluorescence/immunohistochemical Analysismentioning
confidence: 99%
“…In one study in RCC, CD8+ T cell quantification on anti-PD-1 treated RCC samples found a majority of samples (73%) were infiltrated; however, infiltration did not correlate with PFS [69]. In another study, an 11-marker multiplex IF panel-based prognostic score associated with survival of RCC patients, particularly the density of T cell marker CD3-positive cell populations [159]. Interestingly, spatial immune profiling of nephrectomy samples revealed patients with excluded TME had reduced burden of metastatic disease and improved overall survival versus T cell-inflamed TME [160].…”
Section: Immunofluorescence/immunohistochemical Analysismentioning
confidence: 99%
“…Several attempts have been made to develop standardized methods for TIL assessment. For instance, the Immunoscore is a method for (semi-) quantification of CD3 + and CD8 + infiltrating T cells introduced in renal cell carcinoma and colorectal cancer but has not been utilized in SCCHN as a potential diagnostic or prognostic biomarker [ 54 , 75 , 76 , 77 , 78 ]. Recently, the international immunology biomarker working group (IBWG) has designed a guideline-based protocol to assess (stromal and intratumoral) TILs on single slide haematoxilin-eosin (HE) stained sections in several types of solid carcinoma, including SCCHN ( Figure 2 A,B) [ 79 , 80 , 81 ].…”
Section: The Tme In Scchnmentioning
confidence: 99%